2009
DOI: 10.1007/978-0-387-87621-4_27
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Branch Stars and the Ultraviolet Universe

Abstract: Summary. Extremely hot horizontal branch (HB) stars and their progeny are widely considered to be responsible for the "ultraviolet upturn" (or UVX) phenomenon observed in elliptical galaxies and the bulges of spirals. Yet, the precise evolutionary channels that lead to the production of these stars remain the source of much debate. In this review, we discuss two key physical ingredients that are required in order for reliable quantitative models of the UV output of stellar populations to be computed, namely, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Given the small fraction of the lifetime that stars live on the HB, it would require a significant low metallicity main sequence population to exist within these galaxies, which is explicitly ruled out by many studies determining the metallicities of such galaxies. The explanation of these UV upturn galaxies lies in the understanding gleaned from observations of the resolved stellar populations in high metallicity open clusters and socalled "second parameter" globular clusters (Catelan 2009;Peacock et al 2017).…”
Section: Hot Hb Stars As the Source Of The Uv Upturnmentioning
confidence: 99%
“…Given the small fraction of the lifetime that stars live on the HB, it would require a significant low metallicity main sequence population to exist within these galaxies, which is explicitly ruled out by many studies determining the metallicities of such galaxies. The explanation of these UV upturn galaxies lies in the understanding gleaned from observations of the resolved stellar populations in high metallicity open clusters and socalled "second parameter" globular clusters (Catelan 2009;Peacock et al 2017).…”
Section: Hot Hb Stars As the Source Of The Uv Upturnmentioning
confidence: 99%
“…Carter et al (2011) found that the UVX depends more strongly on [α/Fe] than [Fe/H]. An abundance gradient in [α/Fe] could be expected if high amounts of star formation and supernovae increase the α-element enrichment of stars in the bulges of galaxies (Greggio & Renzini 1999;Bressan et al 1994;Catelan 2009). However, Saglia et al (2010) found no obvious gradient in [α/Fe] over the regions we analyze in M31.…”
Section: Galactic Metallicity Gradientmentioning
confidence: 99%
“…Mass loss was applied in its most widely used formulation, namely the Reimers (1975Reimers ( , 1977 formula, with a range of values for the corresponding mass loss "efficiency parameter" η R that allowed us to produce from very red to very blue HB stars. While it is now known that the Reimers formulation does not properly describe mass loss in red giants (e.g., Schröder & Cuntz 2005;Catelan 2008, and references therein), the specific choice of mass loss formalism turns out to be unimportant for our present purposes.…”
Section: Evolutionary Tracks and Interpolation Gridmentioning
confidence: 99%